STRATEGI KAMPANYE DIGITAL PUBLIC RELATIONS DALAM MEMBANGUN REPUTASI MEREK PADA ERA MEDIA SOSIAL - Dhaifina Azizah; Alvira Stevani; Novita Maharani; Rizky Agung Prakoso; Sri Hertimi (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2026)
The massive penetration of the internet and the widespread adoption of social media have reconstructed the paradigm of conventional public relations into Digital Public Relations (Digital PR). In this era of information democratization, brand reputation is no longer a static asset entirely controlled by corporations but rather the result of a constant negotiation of meaning within the cyber realm. This study aims to analyze deeply and holistically the Digital Public Relations campaign strategy in building brand reputation in the social media era. The research method employed a qualitative approach with a descriptive contemporary case study design, supported by in-depth interviews with corporate PR practitioners and social media text analysis utilizing NVivo software. The findings reveal that successful digital reputation management relies on a Multi-platform Convergence Strategy adapted to the sociological characteristics of the audience, including reputation anchoring on Instagram, reputation humanization on TikTok, and real-time engagement on X (Twitter). This integrated campaign effectively converted 68% of cyber sentiments into positive ones by prioritizing a symmetrical two-way communication model (PR 2.0) and digital listening functions. The speed of responding to complaints transparently in the cyber space proved capable of transforming potential crises into authentic proof of corporate accountability. This study provides a theoretical contribution to the enrichment of cyber reputation resilience models and a practical guide for PR practitioners in navigating crisis communication in the digital disruption era.